Institutions and economic development: the “neoliberal” reforms in Latin America - Eyzaguirre, Hugo (1995)
Central issues like a suitable institutional context that allows the market to function and the political consolidation of the reforms are discussed in this article.   A free market con tributes towards economic growth. For that to happen, it is necessary for goods and services to exchange at zero cost. However, these costs are always present in transactions; hence, the market's functioning will depend on the particular institutional context that exists in the economy and on the State's role as supplier of infrastructure and basic social services.   On the other hand, pressure from certain political groups is the cause of numerous State decisions. This important variable suggests a need for the institution of reforms to reduce the government's vulnerability against these groups.